Construction of a 3D brain extracellular matrix model to study the interaction between microglia and T cells in co‐culture. (10th October 2020) - Frühauf, Marie; Zeitschel, Ulrike; Höfling, Corinna; Ullm, Franziska; Rabiger, Friederike V.; Alber, Gottfried; Pompe, Tilo; Müller, Uwe; Roßner, Steffen
Abstract: Neurodegenerative disorders are characterised by the activation of brain‐resident microglia cells and by the infiltration of peripheral T cells. However, their interplay in disease has not been clarified yet. It is difficult to investigate complex cellular dynamics in living animals, and simple two‐dimensional (2D) cell culture models do not resemble the soft 3D structure of brain tissue. Therefore, we developed a biomimetic 3D in vitro culture system for co‐cultivation of microglia and T cells. As the activation and/or migration of immune cells in the brain might be affected by components of the extracellular matrix, defined 3D fibrillar collagen I‐based matrices were constructed and modified with hyaluronan and/or chondroitin sulphate, resembling aspects of brain extracellular matrix. Murine microglia and spleen‐derived T cells were cultured alone or in co‐culture on the constructed matrices. Microglia exhibited in vivo‐like morphology and T cells showed enhanced survival when co‐cultured with microglia or to a minor degree in the presence of glia‐conditioned medium. The open and porous fibrillar structure of the matrix allowed for cell invasion and direct cell‐cell interaction, with stronger invasion of T cells. Both cell types showed no dependence on the matrix modifications. Microglia could be activated on the matrices by lipopolysaccharide resulting in interleukin‐6 and tumour necrosis factor‐α secretion. The findings herein indicate that biomimetic 3D matrices allow for co‐cultivation and activation of primary microglia and T cells and provide useful tools to study their interaction in vitro. Abstract : We developed a biomimetic 3D in vitro culture system for co‐cultivation of microglia and T cells, where defined 3D collagen I‐based matrices were modified with hyaluronan or chondroitin sulphate, resembling aspects of brain extracellular matrix. Murine microglia exhibited in vivo‐like morphology and T cells showed enhanced survival when co‐cultured with microglia. Microglia could be activated on the matrices by lipopolysaccharide resulting in interleukin‐6 and tumour necrosis factor‐α secretion.